CLOSURE OF CAMPONOTUS CHILENSIS (SPINOLA, 1851) (HYMENOPTERA: FORMICIDAE) AGAINST RETICULITERMES FLAVIPES (ROLLAR, 1 8 3 7 ) (ISOPTERA: RHINOTERMITIDAE), UNDER LABORATORY CONDITIONS (Acta Entomológica Chilena, 2022)
The present study was developed with individuáis of the Camponotus chilensis (Spinola, 1851) species and the Reticulitermes flavipes (Kollar, 1837) species under laboratory conditions. The main purpose was to determine the presence of confinement of C. chilensis over R. flavipes and R. flavipes over C. chilensis.To this effect five nests of each species were collected, and they were placed during a one month period of adjustment. After that, the behavior of each the species mentioned above was observed in relation to the presence of invaders of the other species and vice versa. The results obtained were as follows: both species are hermetic and aggressive in relation to invaders of the other one. Both species recognize invaders in the same manner and react at similar time. In relation to the events of aggression, C. chilensispresents a greater frequency of this conduct, and also it does it in less time than the R. flavipes species.
Keywords: Formicidae, Camponotus chilensis, Rhinotermitidae, Reticulitermes flavipes, behavioral events, closure